The monastery entrance: Adventus and path to salvation: With 10 illustrations - Popović Svetlana (Zbornik Radova Vizantološkog Instituta, 2017)
This paper deals with monastic entrance as the liminal architectural element facilitating a transition between outer - lay and inner - sacred worlds. It examines the architectural design and spatial position of the monastery entrance as an articulation of its multiple functions, which apparently crystallized over a long period of time. By the eleventh century the function of a monastic entrance emerged into a codified model that included multiple activities. These undertakings necessitated a further elaboration of its architectural setting including visually recognizable symbolic and prophylactic elements. Symbolically charged visual content of an entrance communicated the messages to both lay people and the monks. For outsiders holy images displayed in the monastic entrance designated the abode for people who live under the protection of celestial beings. At the same time, for insiders (monks and nuns), they had multiple meanings both apotropaic and eschatological signifying an adventus into the other-world, which may open a path to salvation.